Focus : - Ries, Al (Harper Business, 1996)
Shows why companies should focus on core products & get rid of extraneous, energy-wasting ventures. With increased competition & the globalization of business, the future belongs to the company that can narrow its focus in order to dominate its industry. Using examples of companies from a variety of traditional & new industries, Ries offers concrete, no-nonsense advice on how to own a category in the customers mind. He demonstrates how a corporation can increase its competitiveness by narrowing its focus, spinning off divisions that dilute its strength, & establishing a single word or concept the company can own in the mind...